Online Learning during COVID-19 Pandemic Period: Secondary Schools’ Students Perception - Rai, Chandra Badana (KMC Research Journal, 2020)
The COVID-19 has resulted in closure of educational institution across the world. Online learning had played a vital role in the process of teaching and learning during this pandemic. There was a shift of face to face teaching learning to online. The objective of this study was to explore the perception towards online learning of the students of secondary level students. It also identified student responses to online teaching, offered by their schools during the period of the COVID 19 pandemic. This study has utilized a survey research design with a quantitative approach. For this study, secondary level students of Kathmandhu were taken as population. A web-based cross-sectional survey was undertaken among 282 secondary level students from two schools of Kathmandu who had participated in the online classes during this COVID-19 pandemic. A structured questionnaire consisting of 21 items covering students’ perception domain was distributed to the students using Google Form. The study found that the majority of the students 74% were satisfied with online learning. The finding of the study revealed that there was statistically significant in the association of students’ satisfaction in software used in online class since the p value is less than 0.05 and the relationship between the software used in an online class and students’ satisfaction is modest.